Michael Murphy and Jan Smaczny (eds), Music in Nineteenth-Century Ireland (2007) - Bashford, Christina (Journal of the Society for Musicology in Ireland, 2008)
A review of Michael Murphy and Jan Smaczny (eds), Music in Nineteenth-Century Ireland (Dublin: Four Courts Press, 2007), ISBN 978-1-84682-024-3, 336pp, €55